#TITLE_ALTERNATIVE# - SAPUTRA (NIM : 10212001), CASMIKA
In mushroom cultivation are important parameters that must be controlled, the humidity and temperature. Therefore, in this research, temperature and humidity control system for Mushroom House (Kumbung) has been developed. Firstly, simulations created to know spread mechanism of mist (water vapor) in the close room. The spread of mist particles used advection-diffusion models and random walk (Brownian motion) method. In addition to learn about the spread of mist, simulation is used to obtain good control algorithm. Humidifier has been design and built to control the humidity. Optimization of control is done by simulation and experiment. The result humidity control can be optimum in a certain tolerance value. Humidity and temperature monitoring use the internet of things (IoT) concept. So that users can be control Kumbung from anywhere when connect to the Internet.